Keragaan Sosial Ekologi dan Ekonomi Masyarakat Nelayan di Pesisir Cilacap Selatan - Taruna Mona Rachman; Endang Hilmi; Nurul Anwar (Jurnal READ (Research of Empowerment and Development), 2020)
Social ecological system is an ecological system that is closely related and influenced by one or more social systems. Communities in the coastal area of ​​South Cilacap, mostly as capture fisheries, are very dependent on the natural resources of fish in the sea. This study aims to identify social, ecological and economic performance of fishing communities on the coast of South Cilacap. The research method uses quantitative methods with descriptive analysis to analyze the relationships between variables and numerical analysis. The results of this study indicate that social, ecological, and economic performance consists of resources in the form of fish caught at sea, users (fishing communities), various forms of infrastructure and infrastructure providers